THEORETICAL BASIS OF THE USE OF COMPUTER PROGRAMS IN TEACHING (ON THE EXAMPLE OF THE SCIENCE OF MUSIC CULTURE) - Mirzaev Farrux Zayniddinovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article covers the theoretical foundations and stages of development, history of using computer software in teaching music culture science. Also, great attention is paid to the issue of increasing the effectiveness of teaching the science of music culture through computer programs in the training of pedagogical personnel for general music education.